PEMANFAATAN PENDAPATAN PEDAGANG BAKSO IKAN TUNA KELILING DI KOTA AMBON - Hardianti Abubakar; Yolanda MTN Apituley; Lilian Matilda Soukotta (Universitas Pattimura, 2019)
As a form of diversified processed fish meat, tuna meatball is very popular to people in Ambon. This type of food is sold by traders from Java by walking or cycling. Difficulties living in the origin area require traders to leave their families and go out looking for jobs in other areas with hopes that the family needs are met. The purpose of this research is to analyze (1). Characteristics of mobile tuna meatball traders in Ambon, (2). The amount of income received by mobile tuna meatball traders in Ambon, and (3). Percentage income utilized by the mobile tuna meatball traders either in family or personal needs. The study was conducted by survey and data obtained through interviews and observations from May to October 2018. The results show that the average age of meatball traders was between <25-65 yo, having education in junior and senior high school level, with the highest number of dependants 1-2 people and <5 years trading experience. The average income of tuna fish meatball traders is Rp. 4,747,231, - which is used for personal and family needs. Seven traders use more than 50% for family needs and the rest for personal needs, while six traders utilize more than 60 % for personal needs and the rest for family needs.